Opus 13 : Düsseldorf '91 - Ermacora, Beate; Museion - Museum für Moderne Kunst/Museo d'Arte Moderna, Bolzano (Bolzano : Museion - Museo d'Arte Moderna, 1991)
Becker Bernd & Hilla ; Ecker, Bogomir ; Günther, Ingo ; Huber, Thomas ; Lenhart, Johannes ; Luy, Wolfgang ; Mundt, Wilhelm ; Pallanca, Heike ; Pitz, Hermann ; Robbe, Wolfgang ; Rungenhagen, Ulf ; Schütte, Thomas ; Wünkhaus, A.S.
Opus 13 : Düsseldorf '91, Museion - Museo d'Arte Moderna, Bolzano, 1991
boek